Quality of service (QoS) analysis & performance enhancement of mobile communication in Bangladesh - Putul, Badrunnessa; Salam, Humaira (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.